2013
DOI: 10.1186/1752-1947-7-81
|View full text |Cite
|
Sign up to set email alerts
|

Large cell neuroendocrine carcinoma presenting with neck swelling in the submandibular gland: a case report

Abstract: IntroductionLarge cell neuroendocrine carcinoma in the salivary glands is rare. We report a second case of large cell neuroendocrine carcinoma of the submandibular gland diagnosed at autopsy, and a review of the literature.Case presentationA 68-year-old Japanese man was referred to our hospital for thorough investigation of swelling on the right side of his neck. Fine-needle aspiration cytology of the cervical mass suggested poorly differentiated metastatic carcinoma. The primary tumor could not be detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…In their review of 1,675 salivary gland tumors, 2 neoplasms were reclassified as LC-NEC. After these report, others have recognized rare LC-NEC in salivary gland highlighting the benefits of using a standard classification for neuroendocrine carcinomas [20,26].…”
Section: The 2005 World Health Organization (Who)mentioning
confidence: 99%
See 2 more Smart Citations
“…In their review of 1,675 salivary gland tumors, 2 neoplasms were reclassified as LC-NEC. After these report, others have recognized rare LC-NEC in salivary gland highlighting the benefits of using a standard classification for neuroendocrine carcinomas [20,26].…”
Section: The 2005 World Health Organization (Who)mentioning
confidence: 99%
“…Kasafuka et al [17] in a series of 8 mucosal LC-NEC reported that 7 of 8 (80 %) patients presented with regional lymph node metastases and 3 had died of disease after follow-up ranging from 15 to 90 months. Three of 4 (75 %) patients with well documented LC-NEC of the salivary glands have died of their disease [14,20,26]. necrosis''.…”
Section: The 2005 World Health Organization (Who)mentioning
confidence: 99%
See 1 more Smart Citation
“…LCNEC account for less than 1% of all salivary gland tumors. Kawartani, et al [5] reported only eight such cases in a PubMed review of the last 40-years [5]. Most large cell neuroendocrine carcinomas contain the major salivary glands, and especially the parotid gland.…”
Section: Introductionmentioning
confidence: 99%
“…the parotid gland is the second most common site [5,11,12,25]. lCNCs are increasingly being recognized in other sites and have been reported in sinonasal tract [9,26], oral cavity [27], oropharynx [8,28], hypopharynx [8], and submandibular gland [10,29]. Given the limitations of the current WHO classification, which does not make a distinction between moderately differentiated neuroendocrine carcinoma and lCNC, a reliable estimate of the true incidence of lCNC is not possible.…”
mentioning
confidence: 99%